Does board diversity really matter? Gender does not, but citizenship does - Caspar Rose; Peter Munch-Madsen; Maja Funch (International Journal of Business Science & Applied Management (IJBSAM), 2013)
We study the impact of female board representation as well as citizenship on corporate performance based on a sample of the largest listed firms in the Nordic countries as well as Germany. We also seek to determine the variation of board structures using factor analysis. We find no support for any performance impact relating to female board representation. However, we find an impact of board citizenship on performance showing that board members with a background from common law have a significant positive influence on corporate performance measured as ROA, ROE and ROCE. Consistent with other studies we also document that large boards impact corporate performance negatively. Moreover we also show that data set on boards can be explained by four underlying factors. This article adds insight to board determinants of corporate performance as well as the classification of board variation. Specifically, our results support the view that increasing the proportion of board members from common law countries would be beneficial for the largest German and Nordic listed companies.
Keywords: 650; corporate governance; board diversity; gender; citizenship as well as international management